ANALISIS Ca, Mg, KTK DALAM KOMPOS DARI FESES KAMBING PERAH, JERAM, LIMBAH PAKAN HIJAUAN - Yuli Astuti Hidayati; Deden Zamzam Badruzzaman; Eulis Tanti Marlina; Ellin Harlia (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
The research aimed to analyze the quality of compost (Ca, Mg, and CEC content) from various C/N ratios of dairy goat feces, forage waste, and straw. Experimental research methods, the design used a completely randomized design (CRD), using treatment C/N ratio 25 (T1), C/N ratio 30 (T2), and C/N ratio 35 (T3), done six times. The analysis results were tested with variance and Duncan’s test. The research results on the C/N ratio of dairy goat feces, rice straw, and forage waste affect the content of Ca, Mg, and CEC value of compost. For example, the highest content of Ca (19744.04 ± 1570.0 ppm) and Mg (8914.63 ± 670.18 ppm) was obtained in the treatment of C/N ratio 25 (T1), and the highest CEC value (133.61 ± 5.69 cmol/kg) was obtained in the treatment of the C/N ratio 35 (T3).